Feasibility and Accessibility of a Tailored Intervention for Informal Caregivers of People with Severe Psychiatric Disorders: a Pilot Study - Rexhaj, Shyhrete; Leclerc, Claude; Bonsack, Charles; Golay, Philippe; Favrod, Jérôme (Frontiers in Psychiatry, 2017)
Objectives: This study aimed to assess the acceptability and feasibility of a new tailored intervention for informal caregivers: The Ensemble (Together) program. Methods: An open pre-post within-subject comparison pilot study was conducted. Twenty-one informal caregivers completed the five-session Ensemble program. Two measurement tools were used: The Brief Symptom Inventory (BSI) and the Life Orientation scale (LOT-R). Results: The results showed that informal caregivers were in need of individual support and were ready to participate in the Ensemble program independent of the patient’s diagnosis or stage of illness. The participants were very satisfied, and 95.4% completed the program. The preliminary results also showed that in five sessions, informal caregivers’ Global Severity Index measured by the BSI and their optimism about their future (measured by the LOT-R) were significantly improved. Conclusion: This pilot study provided preliminary results concerning the feasibility and acceptability of the tailored Ensemble program and indicate the need for a randomized trial. The Ensemble program is appropriate for both the acute and chronic phases of disease. Individualized brief and useful interventions for informal caregivers may provide more positive outcomes in care.